TRPV Subfamily (TRPV2, TRPV3, TRPV4, TRPV5, and TRPV6) Gene and Protein Expression in Patients with Ulcerative Colitis - Joel J. Toledo Mauriño; Gabriela Fonseca-Camarillo; Janette Furuzawa-Carballeda; Rafael Barreto-Zuñiga; Braulio Martínez Benítez; Julio Granados; Jesus K. Yamamoto-Furusho (Journal of Immunology Research)
Introduction. TRPVs are a group of receptors with a channel activity predominantly permeable to Ca2+. This subfamily is involved in the development of gastrointestinal diseases such as ulcerative colitis (UC). The aim of the study was to characterize the gene and protein expression of the TRPV subfamily in UC patients and controls. Methods. We determined by quantitative PCR the gene expression of TRPV2, TRPV3, TRPV4, TRPV5, and TRPV6 in 45 UC patients (29 active UC and 16 remission UC) and 26 noninflamed controls. Protein expression was evaluated in 5 μm thick sections of formalin-fixed, paraffin-embedded tissue from 5 customized severe active UC patients and 5 control surgical specimens. Results. TRPV2 gene expression was increased in the control group compared with active UC and remission patients (P=0.002 and P=0.05, respectively). TRPV3 gene expression was significantly higher in controls than in active UC patients (P=0.002). The gene expression of TRPV4 was significantly higher in colonic tissue from patients with remission UC compared with active UC patients (P=0.05) and controls (P=0.005). TRPV5 had significantly higher mRNA levels in a control group compared with active UC patients (P=0.02). The gene expression of TRPV6 was significantly higher in the colonic tissue from patients with active UC compared with the control group (P=0.05). The protein expression of TRPV2 was upregulated in the mucosa and submucosa from the controls compared with the UC patients (P≤0.003). The protein expression of TRPV3 and TRPV4 was upregulated in all intestinal layers from the controls compared with the UC patients (P<0.001). TRPV5 was upregulated in the submucosa and serosa from the controls vs. UC patients (P<0.001). TRPV6 was upregulated in all intestinal layers from the UC patients vs. controls (P≤0.001). Conclusion. The TRPV subfamily clearly showed a differential expression in the UC patients compared with the controls, suggesting their role in the pathophysiology of UC.